YES Problem: a(b(x1)) -> b(d(x1)) a(c(x1)) -> d(d(d(x1))) b(d(x1)) -> a(c(b(x1))) c(f(x1)) -> d(d(c(x1))) d(d(x1)) -> f(x1) f(f(x1)) -> a(x1) Proof: String Reversal Processor: b(a(x1)) -> d(b(x1)) c(a(x1)) -> d(d(d(x1))) d(b(x1)) -> b(c(a(x1))) f(c(x1)) -> c(d(d(x1))) d(d(x1)) -> f(x1) f(f(x1)) -> a(x1) Matrix Interpretation Processor: dim=2 interpretation: [1 2] [2] [f](x0) = [0 1]x0 + [0], [c](x0) = x0, [1 1] [1] [d](x0) = [0 1]x0 + [0], [1 3] [3] [a](x0) = [0 1]x0 + [0], [1 0] [0] [b](x0) = [0 3]x0 + [2] orientation: [1 3] [3] [1 3] [3] b(a(x1)) = [0 3]x1 + [2] >= [0 3]x1 + [2] = d(b(x1)) [1 3] [3] [1 3] [3] c(a(x1)) = [0 1]x1 + [0] >= [0 1]x1 + [0] = d(d(d(x1))) [1 3] [3] [1 3] [3] d(b(x1)) = [0 3]x1 + [2] >= [0 3]x1 + [2] = b(c(a(x1))) [1 2] [2] [1 2] [2] f(c(x1)) = [0 1]x1 + [0] >= [0 1]x1 + [0] = c(d(d(x1))) [1 2] [2] [1 2] [2] d(d(x1)) = [0 1]x1 + [0] >= [0 1]x1 + [0] = f(x1) [1 4] [4] [1 3] [3] f(f(x1)) = [0 1]x1 + [0] >= [0 1]x1 + [0] = a(x1) problem: b(a(x1)) -> d(b(x1)) c(a(x1)) -> d(d(d(x1))) d(b(x1)) -> b(c(a(x1))) f(c(x1)) -> c(d(d(x1))) d(d(x1)) -> f(x1) Arctic Interpretation Processor: dimension: 2 interpretation: [f](x0) = x0, [0 -&] [c](x0) = [0 -&]x0, [0 -&] [d](x0) = [0 0 ]x0, [0 0] [a](x0) = [1 2]x0, [0 0] [b](x0) = [0 0]x0 orientation: [1 2] [0 0] b(a(x1)) = [1 2]x1 >= [0 0]x1 = d(b(x1)) [0 0] [0 -&] c(a(x1)) = [0 0]x1 >= [0 0 ]x1 = d(d(d(x1))) [0 0] [0 0] d(b(x1)) = [0 0]x1 >= [0 0]x1 = b(c(a(x1))) [0 -&] [0 -&] f(c(x1)) = [0 -&]x1 >= [0 -&]x1 = c(d(d(x1))) [0 -&] d(d(x1)) = [0 0 ]x1 >= x1 = f(x1) problem: c(a(x1)) -> d(d(d(x1))) d(b(x1)) -> b(c(a(x1))) f(c(x1)) -> c(d(d(x1))) d(d(x1)) -> f(x1) String Reversal Processor: a(c(x1)) -> d(d(d(x1))) b(d(x1)) -> a(c(b(x1))) c(f(x1)) -> d(d(c(x1))) d(d(x1)) -> f(x1) Matrix Interpretation Processor: dim=1 interpretation: [f](x0) = x0 + 4, [c](x0) = x0, [d](x0) = x0 + 2, [a](x0) = x0 + 7, [b](x0) = 8x0 + 9 orientation: a(c(x1)) = x1 + 7 >= x1 + 6 = d(d(d(x1))) b(d(x1)) = 8x1 + 25 >= 8x1 + 16 = a(c(b(x1))) c(f(x1)) = x1 + 4 >= x1 + 4 = d(d(c(x1))) d(d(x1)) = x1 + 4 >= x1 + 4 = f(x1) problem: c(f(x1)) -> d(d(c(x1))) d(d(x1)) -> f(x1) String Reversal Processor: f(c(x1)) -> c(d(d(x1))) d(d(x1)) -> f(x1) Matrix Interpretation Processor: dim=3 interpretation: [1 1 0] [1] [f](x0) = [0 1 0]x0 + [0] [0 0 0] [0], [1 0 1] [0] [c](x0) = [0 1 1]x0 + [1] [0 0 0] [0], [1 0 1] [1] [d](x0) = [0 0 1]x0 + [0] [0 1 0] [0] orientation: [1 1 2] [2] [1 1 2] [2] f(c(x1)) = [0 1 1]x1 + [1] >= [0 1 1]x1 + [1] = c(d(d(x1))) [0 0 0] [0] [0 0 0] [0] [1 1 1] [2] [1 1 0] [1] d(d(x1)) = [0 1 0]x1 + [0] >= [0 1 0]x1 + [0] = f(x1) [0 0 1] [0] [0 0 0] [0] problem: f(c(x1)) -> c(d(d(x1))) Arctic Interpretation Processor: dimension: 3 interpretation: [1 0 0 ] [f](x0) = [-& 0 0 ]x0 [0 -& 1 ] , [1 1 1 ] [c](x0) = [0 0 -&]x0 [1 0 0 ] , [0 -& -&] [d](x0) = [0 -& -&]x0 [0 0 0 ] orientation: [2 2 2] [1 1 1 ] f(c(x1)) = [1 0 0]x1 >= [0 -& -&]x1 = c(d(d(x1))) [2 1 1] [1 0 0 ] problem: Qed